Islamic Economic Views on the Fatwa of the Indonesian Ulema Council (MUI) No. 83 of 2023 - Ulil Albab; Mawardi Mawardi; Elita Fatimatus Salwa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
MUI Fatwa No. 83, which prohibits Israeli goods, might have a substantial impact on Indonesia's Islamic economy, influencing consumption, trade, investment decisions, and halal certification. If adhered to, demand for Israeli goods may fall, while the boycott effort may have an impact on investment decisions and worldwide trade. This can also help Muslims achieve greater unity and ethical consciousness. The author employs literature review methodologies to examine literature relevant to the research issue. The methodology includes a study of Islamic economics based on both bibliographic and secondary data. To get new ideas and information, the method used is analysis approaches such as interpretation, coherence, and heuristics. MUI Fatwa No.83 of 2023 requires legal assistance for the Palestinian fight against Israeli aggression, including the distribution of zakat, infaq, and alms. The fatwa's economic impact is determined by Muslim involvement and business reaction, which may have an impact on halal certification and Sharia banking. MUI Decree Number 83 of 2023 encourages a boycott of Israeli goods, which benefits the Muslim economy while cutting demand